Editorial - Editor, Chief (University of Dar es Salaam Library Journal, 2022)
It is a greater honour to introduce to you Volume 17, Issue 1 (June 2022) of the University of Dar es Salaam Library Journal (UDSMLJ). First and foremost, it would seem well at this point to thank all members of the editorial committee for their invaluable contributions and continued support to this journal. I offer my heartfelt appreciation to all authors and reviewers for their contributions to the journal.